2019
DOI: 10.37762/jgmds.6-1.89
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Accidents Involving Motorcyclists in District Kohat, Pakistan

Abstract: OBJECTIVES:The main aim was to assess the frequencies of accidents of motorbike in previous one year and also to estimate the factors related with the accidents.METHODOLOGY:The study design was quantitative and the data was collected from motorcyclists. In order to collect the primary data; a structured questionnaire was used. We interviewed 412 motorcyclists. Almost all the motorcyclist responded and thus we achieved 99% response. Statistical Package for Social Sciences (SPSS) version 21 was used to enter dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Young riders were associated with risk-taking behaviour, which increase their risk of being involved in motorcycle injuries. Zia-ud-din et al, 12 in their study on the burden of accidents involving motorcyclists in district Kohat, showed that motorcycle accidents most frequently involved younger age groups. The two most frequent age groups were 14-24 years (29.1%) and 25-34 years (41.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Young riders were associated with risk-taking behaviour, which increase their risk of being involved in motorcycle injuries. Zia-ud-din et al, 12 in their study on the burden of accidents involving motorcyclists in district Kohat, showed that motorcycle accidents most frequently involved younger age groups. The two most frequent age groups were 14-24 years (29.1%) and 25-34 years (41.3%).…”
Section: Discussionmentioning
confidence: 99%